Gateways and corridors: Cultural and spatial challenges and opportunities for live music on Australia's Gold Coast. (June 2019) - Green, Ben; Bennett, Andy
Abstract: Both urban planning and academic research are increasingly interested in the notion of the music city and its value in terms of urban (re)generation and creativity. However, for many cities this aspiration may be problematised politically, culturally and indeed physically. Live music on the Gold Coast, Australia is poised for major growth according to participants in the sector, but this demands attention to a range of socio-cultural and spatial factors. Despite a significant history of live music, the Gold Coast is in many ways starting from scratch in developing the necessary hard and soft infrastructure. Geographically, the strip-like city lacks a single live music hub and is located between larger music centres, posing unique challenges as well as opportunities. Based on research undertaken for the City of Gold Coast council, including community consultations, focus groups and individual in-depth interviews, this article investigates the mixed blessings of the Gold Coast as a space for a developing live music sector. Highlights: The Gold Coast, Australia faces cultural and physical challenges in developing a sustainable live music scene. Stakeholder consultation, focus groups and in-depth interviews were conducted in the Gold Coast's live music sector. A rich history of live music culture has to an extent been eclipsed by urban redevelopment. The city's strip-like, patchwork layout and proximity to other live music centres poses challenges and opportunities. This is a case study of a city where aspirations for live music are problematised politically, culturally and physically.